Investigation of the presence of some virulence factors of the Streptococcus pneumoniae isolates among patients in Basra Governora - AlHajem, Halah M.; Almazini, Mohammed A.; Khudaier, Bassam Y. (Iraqi Journal of Science, 2018)
Extensive studies have been conducted on the microbial properties of Streptococcus pneumoniae all over the world ,but there are few studies in Iraq on the most important factors of virulence possessed by S.pneumoniae isolates found in Iraq , 195 of sputum specimens were collected from patients with pneumonia acquired from the community who were clinically diagnosed by specialized doctors depending on symptoms and Radiography of Chest . Eighteen isolates of S.pneumoniae were diagnosed by special traditional methods that used in the phenotypic identification . All isolates 18 (100%) have been given positive results for the optochin test , bile solubility test ,latex agglutination . Genetically , the study of virulence factors was limited to only 11 (61.11%) isolates by using the Polymerase Chain Reaction(PCR) technique, four genes were investigated responsible for virulence factors deemed necessary for S.pneumoniae to colonize and invade the host. The results showed that the isolates of S.pneumoniae in Basra city were fierce ,where the results of PCR amplification showed that the genes CpsA, LytA and Ply were found in all isolates 11 (61.11%) while the Psa gene was present in only 9 (50%) isolates within the current study.